1999
DOI: 10.3109/10799899909036635
|View full text |Cite
|
Sign up to set email alerts
|

Chance Favors the Prepared Mind - From Serendipity to Rational Drug Design

Abstract: Accidental discoveries always played an important role in science, especially in the search for new drugs. Several examples of serendipitous findings, leading to therapeutically useful drugs, are presented and discussed. Captopril, an antihypertensive Angiotensin-converting enzyme inhibitor, was the first drug that could be derived from a structural model of a protein. Dorzolamide, a Carboanhydrase inhibitor for the treatment of glaucoma, and the HIV protease inhibitors Saquinavir, Indinavir, Ritonavir, and Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 43 publications
0
53
0
7
Order By: Relevance
“…Hugo Kubinyi compiled a list of more than 50 examples where important biological activities of substances were found serendipitously (Kubinyi 1999). In many cases, the substances were intended for quite different uses, and their pharmacological potential surfaced unexpectedly in the course of the studies or was found by accident.…”
Section: Rational Drug Design and Its Limitsmentioning
confidence: 99%
“…Hugo Kubinyi compiled a list of more than 50 examples where important biological activities of substances were found serendipitously (Kubinyi 1999). In many cases, the substances were intended for quite different uses, and their pharmacological potential surfaced unexpectedly in the course of the studies or was found by accident.…”
Section: Rational Drug Design and Its Limitsmentioning
confidence: 99%
“…In some of the reconstructions, initial strategies are depicted as "breadth-first" and then after the discovery as "depth-first" [13], using the idea of problem solving as a search in a tree of instances. A search of the first kind, "breadth-first" is usually useful when we do not have a lot of relevant information about the place (inside the "tree") where the solution is.…”
Section: The "Serendipity Mistake" Reconsidered: Blind Searchmentioning
confidence: 99%
“…Considering the large possible chemistry space, it is common to make a selection of compounds for screening. Among the methods used for this task a kind of "diversity" selection is very common [13] (p 87).…”
Section: The "Rational Turn" In Combinatorial Chemistrymentioning
confidence: 99%
See 2 more Smart Citations